Effect of twelve weeks pilates training on functional balance of male patients with multiple sclerosis: Randomized controlled trial. (January 2021) - Gheitasi, Mehdi; Bayattork, Mohammad; Andersen, Lars Louis; Imani, Saeed; Daneshfar, Amin
Abstract: Objective: Pilates training has several well-known benefits for people with Multiple Sclerosis (MS). However, its effect on functional balance is unclear. The present study aimed to evaluate the effect of pilates exercises on the functional balance of male patients with MS. Method: In the present parallel group randomized controlled trial, 30 men with MS were recruited from a local corrective exercise clinic in Tehran, Iran, and randomized into Pilates training group (N = 15), and control group (N = 15). At baseline, the age range was 25–40 years, and disability score index was 3–5. Intervention: The intervention group received Pilates exercises including the extension of the thoracic spine, abdominal strengthening, core stabilizing exercises, upper and lower limb, and posture exercises for 12 weeks. Outcomes: Functional balance assessments including Berg's Balance Scale (BBS) test, Timed Up and Go (TUG) test, and Functional Reach Test (FRT) were measured at the baseline and after 12 weeks. Results: At a 12-week follow-up, a significant between-group difference was observed in favor of the Pilates training group for the functional balance scores (P < 0.05), while no adverse or harmful events were reported in any group. Conclusion: Pilates training increases the functional balance of MS patients, and decreases known risk factors for falls among the patients in this group, which may have the potential to reduce therapeutic costs and can be considered as a complementary therapeutic approach for physical therapists and corrective exercise experts.